GENETIC DIVERSITIES IN THE SIXTH - GENERATION OF SELECTION (S6) OF SOME INBRED LINES OF MAIZE BASED ON THE PHENOTYPIC CHARACTERS AND SSR - Kustanto, Heri; Basuki, Nur; Sugiharto, Arifin Noor; Kasno, Astanto (AGRIVITA, Journal of Agricultural Science, 2012)
The objectives of this research were to find out inbred line diversities based on the phenotype characters and the molecular marker using SSR.Â  The research was performed from February to June 2011, which was divided into field research and laboratory research for molecular analysis. The molecular analysis was conducted at the Biotecnology Laboratory, Faculty of Agriculture, Brawijaya University of Malang. The field trial was done in Kandat, Junrejo, Batu. Materials were used 35 genotypes of maize. Steps for molecular analysis at the laboratory were as followed: (1) DNA isolation, (2) DNA-quality test, (3) PCR SSR, (4) Visualization of the amplification result. The field trial was done by planting genotypes using a RCBD with 2 replications. Result of the dendogram analysis showed that 35 genotypes of maize were divided into 2 main clusters, A and B, that having 35% similarity level. Result for the analysis of variance showed significant difference among genotypes of maize on the entire of the observed phenotype characters. Heritability (H) ranged 61.8% - 98.1%. Coefficient of variance ranged 0.71 â 7.20%. Analysis on the genotypic correlation ranged 0.06 â 1.0. Numbers of rows ear-1 showed significant correlation, in which Jaccardâs similarity coefficient (rs) = +0.43